Acetone Tracer Laser-Induced Fluorescence (LIF) at 282 nm Excitation as a Diagnostic Tool in Elevated Pressure and Temperature Systems. Issue 4 (April 2019) - Hartwig, Jason; Mittal, Gaurav; Sung, Chih-Jen
This paper provides new data at constant pressure, variable temperature and constant temperature, variable pressure over the range of temperature (295–750 K) and pressure (0.5–40 atm), in air and nitrogen bath gases at both constant number density and constant mole fraction needed to enable acetone laser-induced fluorescence (LIF) as a diagnostic tool in an elevated temperature and pressure environment. Results clearly indicate that the effect of elevated pressure on the temperature sensitivity of acetone LIF is negligible when the excitation wavelength is chosen near the absorption maximum, making acetone LIF ideal for measuring temperature fields in high-pressure systems. The data also show that the temperature sensitivity of fluorescence is relatively insensitive to changes in pressure at 282 nm excitation. Furthermore, at 282 nm, fluorescence per mole fraction can be used to extract temperature while fluorescence per molecule is relatively insensitive to temperature, making it optimal for concentration or pressure measurements.